2021
DOI: 10.3390/su13179975
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Trust in Greek Traditional Foods in the Post COVID-19 Era

Abstract: We are entering a new, unprecedented global economic and social era following the COVID-19 pandemic, in which there will be opportunities and threats for the goods and services provided. Traditional foods (TFs) could have their chances in the new food chain which will be developed, as long as they become the food of choice for the consumers of the future. This paper investigates consumers’ trust in Greek TFs, and northwest Greek TFs, in order to assess their potential consumption in the new economy. Trust was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
1
11
0
2
Order By: Relevance
“…In line with previous studies, were identified consumers that consider that the food quality is not verified [25,26]. Thus, there are consumers that trust the meaning of these certifications and choose to buy a more traditional healthy food product [20,21,23,24,35,66].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In line with previous studies, were identified consumers that consider that the food quality is not verified [25,26]. Thus, there are consumers that trust the meaning of these certifications and choose to buy a more traditional healthy food product [20,21,23,24,35,66].…”
Section: Discussionsupporting
confidence: 67%
“…During the COVID-19 pandemic, consumer preferences have leant toward certified foods whose origin is known. Thus, the PDO label begins to become a choice for consumers concerned about their health and a diet that supports their immune system [66,[69][70][71]. Moreover, the traditional shopping system has been altered, so consumers tend to buy healthy food online [72,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify consumers' characteristics beyond the COVID-19 period for Traditional Foods (TFs) we have initiated recently a wide research effort covering different aspects of the subject matter. Our initial findings prove that the "new" consumers trust the TFs as safe, healthy, sustainable, authentic and tasty [44]. They consider traceability regarding questions on package information, on food itself, quality, production process, and personal information important for the purchase of TFs [45].…”
Section: Literature Reviewmentioning
confidence: 59%
“…These cultural foods are passed on from one generation to another [ 3 ] and were common in societies before the modernisation and industrialisation “westernisation” [ 4 ]. There is a general surge in the interest in traditional foods due to the increased awareness of the relationship between diet and non-communicable diseases (NCDs) [ 5 ] and communicable diseases like COVID-19 [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%